1998
DOI: 10.1093/humrep/13.8.2139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seminal plasma on capacitation and hyperactivation in human spermatozoa

Abstract: While hyperactivated motility is known to be a concomitant of capacitation, and a prerequisite for fertilization, the specific interdependence of capacitation and hyperactivation in human spermatozoa has not been investigated. This study was designed to determine the effect of seminal plasma contamination on the expression of hyperactivated motility and the relationship between hyperactivation and capacitation, since seminal plasma contains decapacitation factor(s). Seminal plasma was obtained by centrifugatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
1
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 37 publications
1
86
1
3
Order By: Relevance
“…By contrast, in men with normal sperm morphology, defective ZPIAR is most likely to be due to subtle biochemical or molecular defects in ZP receptors, signal transduction pathways, inefficient cholesterol or zinc removal from the plasma membrane during capacitation, actin polymerization or acrosomal enzyme activation [36][37][38][39][40][41][42]. Several in vitro studies have shown that zinc and SP inhibit sperm capacitation, including hyperactivation and AR, as well as spermatozoa-ZP binding and penetration [17,[20][21][22]. The hyperactivation of capacitated spermatozoa was highly correlated with the ZPIAR [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, in men with normal sperm morphology, defective ZPIAR is most likely to be due to subtle biochemical or molecular defects in ZP receptors, signal transduction pathways, inefficient cholesterol or zinc removal from the plasma membrane during capacitation, actin polymerization or acrosomal enzyme activation [36][37][38][39][40][41][42]. Several in vitro studies have shown that zinc and SP inhibit sperm capacitation, including hyperactivation and AR, as well as spermatozoa-ZP binding and penetration [17,[20][21][22]. The hyperactivation of capacitated spermatozoa was highly correlated with the ZPIAR [43].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that zinc binding to the sperm plasma membrane affects calcium influx through ion competition during capacitation. It is known that SP contains decapacitation factors, as the addition of SP to the culture medium inhibits sperm capacitation and hyperactivated motility, as well as spermatozoa-ZP binding and penetration in vitro [19][20][21][22]. The overall, evidence suggests that a high SP zinc concentration may have a negative impact on the ZPIAR.…”
Section: Introductionmentioning
confidence: 99%
“…Sperm kinetic parameters evaluated included progressively (PRG) motile as well as non-progressive and immotile sperm, curvilinear velocity (VCL; a measure of the total distance travelled by a given sperm during the acquisition divided by the time elapsed); average path velocity (VAP; the spatially averaged path that eliminates the wobble of the sperm head); straight line velocity (VSL; the straight-line distance from beginning to end of track divided by time taken); beat-cross frequency (BCF; frequency of lateral head displacement), ALH (the mean width of sperm head oscillation) and the derivatives, straightness (STR = VSL divided by VAP x 100) and linearity (LIN = VSL divided by VCL x 100, departure of sperm track from a straight line). To be classified as hyperactivated (HYPA), a trajectory had to meet all of the 60 Hz SORT criteria [Mortimer et al, 1998], i.e., VCL ≥ 150 µm/s, LIN ≤ 50% and ALH ≥ 7µm.…”
Section: Motility Assessmentmentioning
confidence: 99%
“…For example, Neill and Olds-Clarke (1987) have shown in mouse sperm that hyperactivation proceeds in the absence of BSA while acrosome-related processes are not observed (chlortetracycline assay). On the other hand, Mortimer et al (1998) reported that hyperactivation of human spermatozoa is inhibited by 5% seminal plasma during capacitation in human tubal fluid whereas acrosome-related processes are observed (chlortetracycline assay). Intracellularly, however, both hyperactivation and the acrosome reaction seem to be triggered by the same signal (Ca 2þ ; Yanagimachi 1994) possibly supported by other second messengers (e.g.…”
mentioning
confidence: 99%